PLAGIARISM IN CLASSIC ARABIC POETICS (COMPARATIVE STUDY OF AL-JUMAHI AND AL-QAIRAWANY’S THOUGHTS) - Muhammad Bachrul Ulum (Arabic Literature Department, 2023)
This research aims to present an interpretation of literary criticism on the occurrence of plagiarism in classical Arabic poetry. The topic of plagiarism, contrasted theoretically, has not been extensively discussed in previous studies. Al-Jumahi was the first to disclose the problematic aspects behind the outstanding reputation of Arab poetry. Conversely, Al-Qairawany presented related theories more systematically. This study employs a descriptive qualitative method using a contrastive approach towards the two major works of these figures, namely Thabaqat Fuhul As-Syuara and Al-Umdah fi Al-Mahasin li As-Syuara wa Adabihi wa Naqdih. The findings reveal that Al-Jumahi and Al-Qairawany start from the same premise, albeit from differing perspectives. Al-Jumahi contends that all forms of imitation are acts of plagiarism, entirely unacceptable in the literary world. On the other hand, Al-Qairawany asserts that if imitation does not compromise the principle of creation and innovation, it can still be accepted as original literary work. Consequently, there is a significant development from the criticism of the Al-Jumahi period to the Al-Qairawany period.